A Secure Medical Information Storage and Sharing Method Based on Multiblockchain Architecture - Hu, Jian; Zhu, Peng; Li, Juanjuan; Qi, Yong; Xia, Youbing; Wang, Fei-Yue (IEEE transactions on computational social systems, 2024)
With the increasing application of technology in the healthcare industry, it has become imperative to establish a robust medical information ecosystem for effective management of medical information secure storage and sharing. This article proposes a healthier ecosystem in collaboration with the main consortium chain and data side chain, using multiblockchain architecture. In the implementation methods for this ecosystem, we store medical information in JavaScript Object Notation (JSON) format within different side chain structures. Additionally, we introduce an improved Practical Byzantine Fault Tolerant (PBFT) consensus mechanism based on a point nomination system and a dynamic RBAC access mechanism. By simulating a blockchain environment with multiple nodes, we analyze the efficiency of this method in terms of record retrieval, consensus mechanism, and storage execution time. The results demonstrate that compared to a single chain structure, the proposed method in this article achieves a substantial 30% improvement in query time efficiency. Moreover, the improved PBFT outperforms the traditional PBFT algorithm without dishonest nodes. Medical records stored in JSON format require shorter storage and execution time compared to text format records. This research contributes toward enhancing the security and efficiency of medical information storage and sharing among different medical subject information systems, thereby fostering a healthier healthcare alliance ecosystem.